The Sagittal Balance Does not Influence the 1 Year Clinical Outcome of Patients With Lumbar Spinal Stenosis Without Obvious Instability After Microsurgical Decompression. Issue 13 (1st July 2015) - Bayerl, Simon Heinrich; Pöhlmann, Florian; Finger, Tobias; Onken, Julia; Franke, Jörg; Czabanka, Marcus; Woitzik, Johannes; Vajkoczy, Peter
<x xml:space="preserve">Abstract</x> Study Design. A retrospective study with retrospective and prospective inclusion of 100 patients. Objective. To determine whether the sagittal balance (SB) influences the clinical outcome of patients with degenerative lumbar spinal stenosis, who underwent microsurgical decompression. Summary of Background Data. The SB has become a critical factor for clinical decision making in the surgical treatment of spinal degenerative diseases. However, a frequently recommended sagittal realignment of elderly, multimorbid patients is accompanied by a significant rate of complications. The influence of SB on the clinical outcome of patients with degenerative spinal stenosis, who undergo decompressive surgery is not well understood. The aim of this study was to explore whether the clinical outcome of these patients is related to the SB and whether patients with spinal stenosis and degenerative sagittal imbalance necessitate restoration of the SB in addition to microsurgical decompression. Methods. One hundred patients with lumbar spinal stenosis, who received microsurgical decompression, were retrospectively identified and classified according to the severity of sagittal imbalance: (1) normal balance group, (2) minor loss of balance group, and (3) major loss of balance group. Sagittal parameters were determined from preoperative lateral spinal radiographs. As outcome parameters, we analyzed pre- and postoperative visual analogue scales for leg and back pain, walking distance, Oswestry disability index, Roland and Morris disability questionnaire, Odom's criteria, and the SF-36 score. Results. All groups significantly benefited from surgery concerning leg pain, back pain, and disability in every day's life. There was no difference in patients with decompensated sagittal imbalance compared to patients with normal SB regarding life quality 6 to 24 months after microsurgical decompression. Conclusions. Patients with symptomatic degenerative spinal stenosis and excluded major instability significantly benefit from microsurgical decompression regardless of their sagittal spinal balance. Thus, restoration of the SB for patients with symptomatic degenerative spinal stenosis cannot be recommended in addition to microsurgical decompression. Level of Evidence: 3